2019
DOI: 10.3389/fnins.2019.01143
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Stair Climbing Training on Postural Control and Sensory Integration Processes in Chronic Post-stroke Patients: A Randomized Controlled Clinical Trial

Abstract: BackgroundPostural control disturbances are one of the important causes of disability in stroke patients affecting balance and mobility. The impairment of sensory input integration from visual, somatosensory and vestibular systems contributes to postural control disorders in post-stroke patients. Robot-assisted gait training may be considered a valuable tool in improving gait and postural control abnormalities.ObjectiveThe primary aim of the study was to compare the effects of robot-assisted stair climbing tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The previous studies confirmed that the paretic leg does not substantially contribute to the postural stability even if the magnitude of WBA was decreased. 27,13,5 Although, the amount of WBA was reduced with a 10 mm insert in the shoe of the nonparetic leg, the balance of the stance was improved but the postural instability could not be significantly changed. 15,16 The general consequence of the balance studies in the poststroke state was that the postural instability depended on the nonparetic leg even if it was loaded with the majority of weight 7,13,26 According to daily practice and comparing studies of the equilibrium of patients in the poststroke state, balance cannot be effectively influenced by physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous studies confirmed that the paretic leg does not substantially contribute to the postural stability even if the magnitude of WBA was decreased. 27,13,5 Although, the amount of WBA was reduced with a 10 mm insert in the shoe of the nonparetic leg, the balance of the stance was improved but the postural instability could not be significantly changed. 15,16 The general consequence of the balance studies in the poststroke state was that the postural instability depended on the nonparetic leg even if it was loaded with the majority of weight 7,13,26 According to daily practice and comparing studies of the equilibrium of patients in the poststroke state, balance cannot be effectively influenced by physiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The general consequence of the balance studies in the poststroke state was that the postural instability depended on the nonparetic leg even if it was loaded with the majority of weight 7,13,26 According to daily practice and comparing studies of the equilibrium of patients in the poststroke state, balance cannot be effectively influenced by physiotherapy. 25,24,27 It may mean that the persistence of the postural instability after restoration of paresis threatens the quality of life after stroke. In this respect, our observation, that the balance instability remains for years after stroke is important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G-EO system was a commercialized end-effector robot that could simulate stair climbing in a treadmill-like environment by moving foot plates in cycle to reproduce step length and height of stairs, but the system was bulky and stationary. The RCT evaluated the stair version of G-EO system focused on balance training of chronic stroke subjects [36]. Portablepower ankle-foot orthosis (PPAFO) developed in the University of Illinois used a pneumatic bidirectional rotatory actuator to provide untethered ankle assistance on level ground and stairs.…”
Section: Discussionmentioning
confidence: 99%
“…G-EO system was a commercialized end-effector robot that could simulate stair climbing in a treadmill-like environment by moving foot plates in cycle to reproduce step length and height of stairs, but the system was bulky and stationary. The randomized controlled trial (RCT) evaluated the stair version of G-EO system focused on balance training of chronic stroke subjects [ 20 ]. Portable-power ankle–foot orthosis developed in the University of Illinois used a pneumatic bidirectional rotatory actuator to provide untethered ankle assistance on level ground and stairs.…”
Section: Introductionmentioning
confidence: 99%